THE EFFECT OF CORPORATE GOVERNANCE MECHANISM ON BOND RATINGS OF PUBLIC COMPANIES IN INDONESIA - I Putu Kamyarta Ariwangsa; Nyoman Abundanti (Forum Manajemen, 2013)
Corporate governance mechanism is a system of corporate governance,which refers to the division of authority between all parties (shareholders, managementand board of directors) that determines the direction and financial performance.This study aimed to determine the effect of corporate governance mechanismsare proxied by institutional ownership, independent commissioners, managerialownership, quality audit and the audit committee of the company’s bond ratings onIndonesian public. The population in this study is that corporate bonds listed on theIndonesia Stock Exchange and is still in circulation from 2008 to 2010. Method ofsampling done by purposive sampling method, and based on the criteria specifiedthen the number of samples were 140 samples. Hypothesis testing techniques usedmultiple linear regression analysis with the tools of SPSS version 18.0 applications. The results showed that: (1) corporate governance mechanisms are proxied by anindependent commissioner, audit quality and audit committee significant positiveeffect on bond ratings. (2) two other proxy of institutional ownership and managerialownership is not a significant positive effect on corporate bond ratings. Based onthe results of the study suggested further research to investigate using other proxiesof corporate governance mechanisms such as by using the Corporate GovernancePerception Index (CGPI) as additional variables that are used in this study.